Comparison of ultrasound phacoemulsification and FemtoMatrix® PhotoEmulsification® cataract surgery - de Saint Jean, Amélie; Dufournel, Damien; Stodulka, Pavel; Romano, Fabrice; Bernard, Aurélien (Frontiers in Medicine, 2023)
Objective: To introduce a novel technology currently under final development before regulatory approvals for the furtherment of cataract surgery, using the FemtoMatrix® laser system, and to demonstrate its safety and efficacy as compared to standard ultrasound phacoemulsification. Methods: Thirty-three patients with bilateral cataracts were operated on with one eye undergoing PhotoEmulsification® treatment on the FemtoMatrix® device and the contralateral eye receiving the control procedure i.e., standard ultrasound phacoemulsification treatment. The number of “zero-phaco” procedures (denoting that I/A alone was sufficient to aspirate the lens fragments and that no ultrasound energy was needed) was recorded and Effective Phaco Time (EPT) values were compared. The patient follow-up was three months. Results: Thirty-three eyes from a population with a mean cataract grade of 2.6 were treated on the FemtoMatrix®, of which 29 were “zero-phaco” (88%). All patients were operated on by a single surgeon who was a relative novice to the technology (63 patients treated prior to this study). Conversely, of the 33 fellow eyes who underwent standard ultrasound phacoemulsification, none were zero-phaco (0%) - all required varying degrees of ultrasound energy to make lens aspiration possible. The mean EPT was significantly lower in the PhotoEmulsification® laser group (0.2±0.8 seconds) than in the phaco group (1.3±1.2 seconds) (P<0.0001). The safety profiles of the two procedures were comparable, with no device-related adverse events noted. Conclusion: FemtoMatrix® is a promising femtosecond laser platform that, when compared to phacoemulsification, significantly decreases or eliminates EPT altogether. The system is used to perform PhotoEmulsification®, making zero-phaco cataract procedures feasible including in high-grade cataracts (>3). It enables personalized treatment by automatically measuring and adapting the laser energy required to obtain the most efficient cutting of the crystalline lens. This new technology appears to be safe and effective in cataract surgery.